Tree age affects physicochemical, functional quality and storability of Amrapali mango (Mangifera indica L.) fruits. (6th February 2018) - Meena, Nirmal Kumar; Asrey, Ram
Abstract: BACKGROUND: The effect of tree age on physicochemical quality attributes and storage behaviour of Amrapali mango fruit was evaluated. Physiologically mature fruits were harvested from 6‐, 18‐ and 30‐year‐old trees and kept for ripening under ambient conditions (temperature 35 ± 3 °C, relative humidity 60 ± 5%). Observations were recorded at 3‐day intervals. RESULTS: Highest total soluble solids and total sugars were found in the fruit sourced from 18‐year‐old trees. At the end of storage, least titratable acidity (0.17%) and higher carotenoids (10.86 mg 100 g −1 ) were found in 30‐year‐old tree fruits during the last day of storage. Highest total phenols (TP) (251.33 μg gallic acid g −1 ), antioxidant capacity (AC) (5.63 μmol Trolox g −1 ) and ascorbic acid (AA) (31.13 mg 100 g −1 ) were reported in fruits from younger trees of 6 years old. Maximum respiratory and ethylene evolution peak was observed in fruits obtained from oldest trees, whereas least activities of pectin methyl esterase (0.31 μmol min −1 g −1 fresh weight) and polygalacturonase (53.67 μg galacturonic acid g −1 h −1 ) were observed in 6‐year‐old tree fruits at the end of the 9‐day storage period. CONCLUSION: Higher total soluble solids and total sugars were found in fruit harvested from middle‐age‐group (18‐year‐old) trees during the entire storage period of 9 days. Most of the functional parameters, such as TP, AC and AA, were observed to be higher in fruits from younger (6‐year‐old) trees. The obtained results revealed that produce from middle‐age‐group (18‐year‐old) Amrapali mango orchards suit consumers' and processors' requirements. © 2017 Society of Chemical Industry